A proof of concept using the Ussing chamber methodology to study pediatric intestinal drug transport and age‐dependent differences in absorption - Eva J. Streekstra; Márton Kiss; Jeroen van denHeuvel; Johan Nicolaï; Petra van denBroek; Sanne M. B. I. Botden; Martijn W. J. Stommel; Lara vanRijssel; Anna‐Lena Ungell; Evita van deSteeg; Frans G. M. Russel; Saskia N. deWildt (Wiley, 2022)
Abstract Little is known about the impact of age on the processes governing human intestinal drug absorption. The Ussing chamber is a system to study drug transport across tissue barriers, but it has not been used to study drug absorption processes in children. This study aimed to explore the feasibility of the Ussing chamber methodology to assess pediatric intestinal drug absorption. Furthermore, differences between intestinal drug transport processes of children and adults were explored as well as the possible impact of age. Fresh terminal ileal leftover tissues from both children and adults were collected during surgery and prepared for Ussing chamber experiments. Paracellular (enalaprilat), transcellular (propranolol), and carrier‐mediated drug transport by MDR1 (talinolol) and BCRP (rosuvastatin) were determined with the Ussing chamber methodology. We calculated apparent permeability coefficients and efflux ratios and explored their relationship with postnatal age. The success rate for the Ussing chamber experiments, as determined by electrophysiological measurements, was similar between children (58%, N = 15, median age: 44 weeks; range 8 weeks to 17 years) and adults (67%, N = 13). Mean serosal to mucosal transport of talinolol by MDR1 and rosuvastatin by BCRP was higher in adult than in pediatric tissues (p = 0.0005 and p = 0.0091). In contrast, within our pediatric cohort, there was no clear correlation for efflux transport across different ages. In conclusion, the Ussing chamber is a suitable model to explore pediatric intestinal drug absorption and can be used to further elucidate ontogeny of individual intestinal pharmacokinetic processes like drug metabolism and transport.